The Influence of Principal Instructional Leadership and School Culture on Teacher Performance for Advancing Sustainable Quality Education - Mega Mustika Ali; Ahmad Sabandi; Nurhizrah Gistituati; Anisah (Postgraduate, University of Mataram, 2026)
Teacher performance (TP) is a key determinant of educational quality, making it important to understand the organizational factors that enhance teachers’ effectiveness. This study examined the influence of principal instructional leadership (PIL) and school culture (SC) on TP among senior high school teachers. A quantitative research design was employed involving 261 teachers from 19 public senior high schools in one regency of Jambi Province, Indonesia, selected through proportionate stratified random sampling. Data were collected using Likert-scale questionnaires and analyzed using descriptive statistics, simple linear regression, and multiple linear regression. The results indicated that both PIL and SC had significant positive effects on TP. Compared with PIL, SC contributed more strongly to teacher performance. Moreover, the combined effects of PIL and SC explained teacher performance better than either variable individually, suggesting that effective instructional leadership and a positive school culture jointly enhance teachers’ professional performance. These findings highlight the importance of strengthening instructional leadership practices while fostering a supportive school culture to improve teacher performance and promote educational quality. The study concludes that integrating effective leadership with a positive organizational culture provides a practical strategy for enhancing teacher performance in senior high schools.